2007
DOI: 10.1097/01.ana.0000211025.41797.fc
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of 5-HT3 Receptor Antagonists for the Prevention of Postoperative Nausea and Vomiting After Craniotomy: A Meta-Analysis

Abstract: The purpose of this meta-analysis was to assess the efficacy of prophylactic administration of 5-HT3 receptor antagonists for postoperative nausea and vomiting in neurosurgical patients at 24 and 48+ hours. After a systematic search, 7 published randomized placebo controlled trials involving 448 craniotomy patients (222 treatment, 226 control) were included in the meta-analysis. Study drugs included ondansetron, granisetron, and tropisetron. The cumulative incidence of emesis was significantly reduced in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…Our results are similar to that of other authors and a Meta-analysis who have reported lower efficacy of 5HT3 antagonist for nausea. [1210] Retching was highest in group D (16%) and least in group G (4%). Most of the studies on PONV in patients undergoing craniotomy have not commented on the incidence of retching as a separate symptom.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results are similar to that of other authors and a Meta-analysis who have reported lower efficacy of 5HT3 antagonist for nausea. [1210] Retching was highest in group D (16%) and least in group G (4%). Most of the studies on PONV in patients undergoing craniotomy have not commented on the incidence of retching as a separate symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on PONV in patients undergoing craniotomy have not commented on the incidence of retching as a separate symptom. [123] Post-operative retching is the most neglected PONV symptom, which by causing increase in arterial and intracranial pressure may cause major medical morbidity and therefore should be properly addressed in post craniotomy patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8] One of them, Carlisle and Stevenson, 8 Nevertheless, starting in 2010, several significant things happened almost simultaneously. Although they all seemed to have contributed to Fujii's end, it is speculation as to whether they actually influenced each other.…”
mentioning
confidence: 99%